Service model based on Lean Service: Standardized Work and 5S to increase customer satisfaction in a veterinary SME - Collao Diaz, Martin Fidel (2023)
Companies in the veterinary services sector face the challenge of providing optimal customer service. This sector contributes 40% of the national Gross domestic product and concentrates 48% of formal employment. Considering that, customer satisfaction is one of the key factors to achieve reliable results in our organizations. The low level of this was identified as one of the main problems of the sector, which may be due to different inefficiencies such as low service quality, unsatisfied demand, extended service times and long waits. In this way, a model based on the Lean methodology and the application of 5S tools and standardized work was developed to increase customer satisfaction. It was validated by conducting a case study in a company in the sector located in the Peruvian province of Callao. The results showed an increase in workers efficiency to 90%, a 4.8" decrease in tools searching time and a 25% increase in the Net Promoter Score.